Auditory localisation of conventional and electric cars: Laboratory results and implications for cycling safety. (August 2016) - Stelling-Kończak, Agnieszka; Hagenzieker, Marjan; Commandeur, Jacques J.F.; Agterberg, Martijn J.H.; van Wee, Bert
Highlights: We studied auditory localisation of electric and conventional cars in three age groups. Participants were worse at indicating the location of electric car sounds. Older age and low car speeds were associated with lower localisation accuracy. Higher ambient sound was associated with lower localisation accuracy. Location of car sounds coming from directly behind the listener was least accurate. Abstract: When driven at low speeds, cars operating in electric mode have been found to be quieter than conventional cars. As a result, the auditory cues which pedestrians and cyclists use to assess the presence, proximity and location oncoming traffic may be reduced, posing a safety hazard. This laboratory study examined auditory localisation of conventional and electric cars including vehicle motion paths relevant for cycling activity. Participants ( N  = 65) in three age groups (16–18, 30–40 and 65–70 year old) indicated the location and movement direction (approaching versus receding) of cars driven at 15, 30 and 50 km/h in two ambient sound conditions (low and moderate). Results show that low speeds, higher ambient sound level and older age were associated with worse performance on the location and motion direction tasks. In addition, participants were less accurate at determining the location of electric and conventional car sounds emanating from directly behind the participant. Implications for cycling safety and proposals for adding extra artificial noise or warning sounds to quiet (electric) cars are discussed.